Man in the “Splendour of Divinity.” The Hagiological Interpretation of “spousal love” in line with John Paul II’s Theology of the Body - Parzych-Blakiewicz, Katarzyna (Teologia w Polsce, 2020)
The article presents the theological interpretation of the phenomenon of spousal love in terms of examining its correlations with the call to holiness. This study belongs to the field of hagiological research aiming at developing a new concept that defines arguments in the Church’s strategy concerning the defence of every human life. The analysis concerns the statements and philosophical writings of Karol Wojtyła and then John Paul II on spousal love and the dependence of the person and his actions on the Truth and Good. The Christological-soteriological aspect of spousal love as conditioning the sanctification of the person has been indicated. The axiological conditions related to the Christological assumption have been termed as “the Splendour of Divinity,” identifying it with the space of the salvific influence on a person, sanctified by Christ’s spousal love and called to develop an ethos based on this love.